2022
DOI: 10.1021/acsnano.1c05901
|View full text |Cite
|
Sign up to set email alerts
|

Scratching the Surface of the Protein Corona: Challenging Measurements and Controversies

Abstract: This Review aims to provide a systematic analysis of the literature regarding ongoing debates in protein corona research. Our goal is to portray the current understanding of two fundamental and debated characteristics of the protein corona, namely, the formation of mono- or multilayers of proteins and their binding (ir)­reversibility. The statistical analysis we perform reveals that these characterisitics are strongly correlated to some physicochemical factors of the NP–protein system (particle size, bulk mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 175 publications
5
52
0
Order By: Relevance
“…The results of these two tests showed the exchange of the preadsorbed proteins with proteins from the medium and confirmed the reversibility of the adsorption process, even for a strongly adsorbing protein such as LYZ, in agreement with the earlier observations from the adsorption isotherm and the dilution experiment. A simple exponential decay model, based on a pseudo‐first order kinetics, [ 15 ] was used to model both adsorption and desorption experiments. Because the total protein concentration (labeled and unlabeled) was constant in both experiments, it was expected that both exchange rate constants k of adsorption and desorption match.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of these two tests showed the exchange of the preadsorbed proteins with proteins from the medium and confirmed the reversibility of the adsorption process, even for a strongly adsorbing protein such as LYZ, in agreement with the earlier observations from the adsorption isotherm and the dilution experiment. A simple exponential decay model, based on a pseudo‐first order kinetics, [ 15 ] was used to model both adsorption and desorption experiments. Because the total protein concentration (labeled and unlabeled) was constant in both experiments, it was expected that both exchange rate constants k of adsorption and desorption match.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was demonstrated that the monolayer is the most prevalent structure of the PC, but that multilayer could be favored under specific circumstances related to the NP physicochemical nature (e.g., size and type of NP material). [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 , 21 We recently demonstrated that preclinical and clinical nanoparticles trigger complement via binding of natural antibodies. 22 We and others previously observed that complement activation pathways and processes depend on the nanoparticle size/curvature, ligand spacing, and density 23 , 24 and are modulated by a dynamic “protein corona”. 25 27 A recent all-atom molecular dynamics simulation concluded strong interactions between SARS-CoV-2 RBD and albumin as well as apolipoprotein E. 28 , 29 Such modes of interaction may mask the binding of neutralizing antibodies and limit complement activation.…”
mentioning
confidence: 97%
“…Antibodies can activate complement via the classical pathway (CP) through C1q binding to the Fc portions of adjacent IgG and the lectin pathway (LP) through binding of mannan-binding lectin, collectins, and ficolins to glycosylated IgG residues. , In addition to these, IgG can enhance C3 deposition by acting as a scaffold for initial C3b binding and subsequently amplify C3b deposition through the assembly of the alternative pathway (AP) convertase. , We recently demonstrated that preclinical and clinical nanoparticles trigger complement via binding of natural antibodies . We and others previously observed that complement activation pathways and processes depend on the nanoparticle size/curvature, ligand spacing, and density , and are modulated by a dynamic “protein corona”. A recent all-atom molecular dynamics simulation concluded strong interactions between SARS-CoV-2 RBD and albumin as well as apolipoprotein E. , Such modes of interaction may mask the binding of neutralizing antibodies and limit complement activation. Thus, by considering the dynamics of the protein corona, it would be essential to map out the role of neutralizing anti-SARS-CoV-2 antibodies in complement activation and C3 opsonization in full sera as well as complement-mediated leukocyte responses in whole human blood.…”
mentioning
confidence: 99%